1
$\begingroup$

Evaulate :

$$ \frac{1}{\log_{xy} (xyz)} + \frac{1}{\log_{yz} (xyz)} + \frac{1}{\log_{zx} (xyz)} $$

I think that the following property of log will be used:

$$ \log_a (b) * \log_b (c) * log_c (a) = 1 $$

But I don't know how?

$\endgroup$
5
$\begingroup$

Use the fact that

$$\log_a b = \frac{\ln b}{\ln a}.$$

Thus

$$\frac{1}{\log_{xy}(xyz)} = \frac{\ln (xy)}{\ln(xyz)}$$

etc.

$\endgroup$
2
$\begingroup$

By using the identity $$ \log_b(a)=\frac{\ln{a}}{\ln{b}} $$ Your equation becomes: $$ \frac{\ln (x y)}{\ln (x y z)}+\frac{\ln (x z)}{\ln (x y z)}+\frac{\ln (y z)}{\ln (x y z)}$$ Which you could further simplify to (using the identity $\ln{(a\times b)}=\ln{a}+\ln{b}$:

$$ \frac{\ln (x y)+\ln (x z)+\ln (y z)}{\ln (x y z)}= \frac{2\ln (x)+2\ln (y)+2\ln (z)}{\ln (x y z)} =\frac{2(\ln (x)+\ln (y)+\ln (z))}{\ln (x y z)}$$ $$=\frac{2(\ln (x y z ))}{\ln (x y z)}=2$$

$\endgroup$
1
$\begingroup$

Hint :

$$\log (ab)=\log a + \log b$$

$$\log_a a=1$$

$$\log_a b = \frac{\log b}{\log a}$$

I am in hurry.. Please see if this can help you... If not i hope some one would help...

$\endgroup$
  • $\begingroup$ isn't $$ \log_a (b) = \frac {log_c (b)}{log_c (a)}$$ ?? $\endgroup$ – kartikeykant18 Apr 16 '14 at 12:18
  • $\begingroup$ @kool_kartikey : Both are one and the same... I should have been careful though! $\endgroup$ – user87543 Apr 17 '14 at 5:38

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.